Circulating MicroRNAs as Diagnostic Biomarkers of Clinical Cognitive Impairment: A Meta-Analysis. (22nd October 2020) - Shi, Dan; Han, Mengyu; Liu, Weilin; Tao, Jing; Chen, Lidian
Background: Minimally invasive diagnostic biomarkers of neurodegenerative diseases such as Alzheimer's disease (AD) facilitate patient selection and cognitive progressive decline monitoring. However, the diagnostic value of circulating microRNAs (miRNAs) for early cognitive impairment and progression to dementia is currently under debate. Thus, this study aimed to assess the diagnostic performance of circulating, cerebrospinal fluid (CSF) and exosomal miRNAs in the detection of clinical cognitive impairment in mild cognitive impairment (MCI), AD, and MCI-AD. Methods: We searched PubMed, Embase, Web of Science, China National Knowledge Infrastructure (CNKI), VIP Chinese Science and Technology Journals Database (CQVIP), and Chinese Medicine Premier (Wanfang) to identify potentially eligible studies related to noncoding RNAs and cognitive dysfunction biomarkers published before November 2018. The quality assessment of the studies was performed according to the Quality Assessment of Diagnostic Accuracy Studies (QUADAS-2) checklist. Meta-analysis of the literature data was performed using Stata/MP 14.0 software. The corresponding effects models were selected to calculate the summary sensitivity, specificity, positive and negative likelihood ratios (PLR and NLR), and diagnostic odds ratio (DOR) and to plot the summary receiver operating characteristic curves (SROCs) and calculate the areas under the curves (AUCs). Results: A total of 18 studies involving 729 patients with AD, 283 patients with MCI, and 15 patients with MCI-AD were pooled. The results revealed that the sensitivity and specificity of miRNAs in the diagnosis of AD were 0.78 and 0.79, respectively, and the area under the summary receiver operating characteristic curve (AUSROC) was 0.90. The sensitivity and specificity of miRNAs in the diagnosis of MCI were 0.89 and 0.85, respectively, and the AUSROC was 0.94. The sensitivity and specificity of microRNAs in the diagnosis of MCI-AD were 0.87 and 0.84, respectively, and the AUSROC was 0.92. Conclusion: Our study found that miRNAs have certain diagnostic value for cognitive impairment, with high sensitivity and specificity, especially in diagnostics with multiple miRNAs and serum-based miRNA assays.